DISCOVER: Dutch Iliac Stent trial: COVERed balloon-expandable versus uncovered balloon-expandable stents in the common iliac artery: study protocol for a randomized controlled trial - Bekken Joost A; Vos Jan Albert; Aarts Ruud A; de Vries Jean-Paul PM; Fioole Bram (Trials, 2012)
Abstract Background Iliac artery atherosclerotic disease may cause intermittent claudication and critical limb ischemia. It can lead to serious complications such as infection, amputation and even death. Revascularization relieves symptoms and prevents these complications. Historically, open surgical repair, in the form of endarterectomy or bypass, was used. Over the last decade, endovascular repair has become the first choice of treatment for iliac arterial occlusive disease. No definitive consensus has emerged about the best endovascular strategy and which type of stent, if any, to use. However, in more advanced disease, that is, long or multiple stenoses or occlusions, literature is most supportive of primary stenting with a balloon-expandable stent in the common iliac artery (Jongkind V et al., J Vasc Surg 52:1376-1383,2010). Recently, a PTFE-covered balloon-expandable stent (Advanta V12, Atrium Medical Inc., Hudson, NH, USA) has been introduced for the iliac artery. Covering stents with PTFE has been shown to lead to less neo-intimal hyperplasia and this might lower restenosis rates (Dolmatch B et al. J Vasc Interv Radiol 18:527-534,2007, Marin ML et al. J Vasc Interv Radiol 7:651-656,1996, Virmani R et al. J Vasc Interv Radiol 10:445-456,1999). However, only one RCT, of mediocre quality has been published on this stent in the common iliac artery (Mwipatayi BP et al. J Vasc Surg 54:1561-1570,2011, Bekken JA et al. J Vasc Surg 55:1545-1546,2012). Our hypothesis is that covered balloon-expandable stents lead to better results when compared to uncovered balloon-expandable stents. Methods/Design This is a prospective, randomized, controlled, double-blind, multi-center trial. The study population consists of human volunteers aged over 18 years, with symptomatic advanced atherosclerotic disease of the common iliac artery, defined as stenoses longer than 3 cm and occlusions. A total of 174 patients will be included. The control group will undergo endovascular dilatation or revascularization of the common iliac artery, followed by placement of one or more uncovered balloon-expandable stents. The study group will undergo the same treatment, however one or more PTFE-covered balloon-expandable stents will be placed. When necessary, the aorta, external iliac artery, common femoral artery, superficial femoral artery and deep femoral artery will be treated, using the standard treatment. The primary endpoint is absence of binary restenosis rate. Secondary endpoints are reocclusion rate, target-lesion revascularization rate, clinical success, procedural success, hemodynamic success, major amputation rate, complication rate and mortality rate. Main study parameters are age, gender, relevant co-morbidity, and several patient, disease and procedure-related parameters. Trial registration Dutch Trial Register, NTR3381.